Economic sanctions and domestic debt: Burundi's fiscal response to the suspension of budget support - Roel Dom; Lionel Roger (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2018)
Economic sanctions, and the suspension of budget support in particular, are supposed to pressure target governments to comply with donors' demands by putting spending commitments at risk. We argue that this is too simplistic since governments have more fiscal levers at their disposal. The case of Burundi illustrates this argument. Following Burundi's 2015 political crisis, donors imposed economic sanctions on the country and suspended all budget support to the national government. Using monthly data on the government's fiscal position between 2005 and 2017, we present evidence from a time series analysis showing that aid does not affect spending and that aid shortfalls are instead systematically compensated with domestic borrowing. It appears that the Burundian government has been able to withstand the sanctions and to fulfill its spending commitments by substituting domestic debt for aid. Thus, the economic costs of sanctions do not necessarily translate directly into political costs but are mitigated by the government's fiscal response.
Keywords: 330; Burundi; Economic Sanctions; Aid; Domestic Debt; Fiscal Response